EFFORTS TO IMPROVE CHILDREN'S ART ABILITY THROUGH FINGER PAINTING ACTIVITIES IN CHILDREN AGED 5-6 YEARS - Jumiati; Nirwana; Supriadi (Media Inovasi Pendidikan dan Publikasi, 2023)
The low ability of children's art is caused by various things, one of which is limited resources, learning approaches, methods and media used have not fully facilitated children to support children's art learning. To overcome this, one way that can support the achievement of children's visual arts abilities is through finger painting activities. The subjects in this study were 10 students of grade B RA Ihya Al Ulum UIM. Consists of 7 boys and 3 girls, and the age range is 5-6 years. This classroom action research was conducted in two cycles and in each cycle two meetings were held. The focus of this research is to improve children's art skills through finger painting activities. Research procedures include planning, implementation, observation and reflection. The data collection technique used is observation and documentation. The results showed that children developed very well (BSB) with a percentage in cycle one, which was 40% and in cycle two, it reached 80%. It can be concluded that by implementing finger painting activities, it can improve children's visual arts abilities in children aged 5-6 at RA Ihya Al Uum UIM. This can be seen from the stages of child development from each meeting in both cycles, after the application of finger painting activities in early childhood.